Human umbilical cord mesenchymal stem cell-derived exosomes repair IBD by activating the SIRT1-FXR pathway in macrophages - Mengjiao Zhou; Bing Pei; Peipei Cai; Chengxue Yi; Francis Atim Akanyibah; Changkun Lyu; Fei Mao (Stem Cell Research & Therapy)
Abstract Background Inflammatory bowel disease (IBD), a chronic immune disorder, has increasing global incidence and poor treatment outcome. Abnormal macrophage function is implicated in the pathophysiology of IBD. In this study, we investigated the mechanism by which human umbilical cord mesenchymal stem cell-derived exosomes (hucMSC-Ex) inhibit inflammation in IBD mouse and macrophage inflammation models. Methods We established a dextran sodium sulfate (DSS)-induce BALB/c mice model of IBD and treated with hucMSC-Ex via tail vein to evaluate their repair effect on IBD mice. An in vitro macrophage inflammation model was established using lipopolysaccharide (LPS) and Nigericin (Nig) by stimulating mouse macrophage RAW264.7 and human myeloid leukemia mononuclear (THP-1) cells to assess the repair effect of hucMSC-Ex on macrophage inflammation. EX 527, an effective inhibitor of silent information regulator of transcription 1 (SIRT1), was employed in both the in vivo and in vitro models to explore the effect of hucMSC-Ex on the SIRT1-FXR (farnesoid X receptor) pathway in macrophages during the attenuation of inflammation. Results HucMSC-Ex effectively inhibited inflammation in both the in vivo and in vitro models by up-regulating the expressions of SIRT1 and FXR, which reduced the acetylation level of FXR and inhibited the activation of NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome. The addition of EX 527 further proved that hucMSC-Ex can reduce the acetylation of FXR by activating the SIRT1-FXR pathway, and the decrease of FXR acetylation was directly related to the inhibition of the activity of the NLRP3 inflammasome. Conclusion HucMSC-Ex alleviates IBD by reducing the acetylation level of FXR through activating the SIRT1-FXR pathway in macrophages and directly negatively regulating the activation of NLRP3 inflammasomes, thus inhibiting the occurrence of the inflammatory process.